Probabilistic seismic hazard analysis of Nepal - Ghimire, Sunita (Journal of Innovations in Engineering Education, 2019)
Probabilistic seismic hazard analysis for Nepal has been carried out considering uniform density model. A detailed earthquake catalogue since 1255 A.D, within the rectangular area has been developed and historical earthquakes are plotted in the map of Nepal. Five hundred twenty eight numbers of areal sources are used within the study area to characterize the seismic sources. The completeness of the data has been checked by using Stepp's procedure. Seismicity in four regions of study area has been evaluated by defining 'a' and 'b' parameters of Gutenberg Richter recurrence relationship. Seismic hazard curve of Nepal for soft subsoil condition for 10% probability of exceedence in 50 years period i.e. for return period of 475 years has been plotted.